PROFESSIONAL AND PEDAGOGICAL QUALITIES IN DEVELOPING THE ARTISTIC AND CREATIVE SKILLS OF THE STUDENTS OF THE FINE ARTS AND ENGINEERING GRAPHICS - Ikromov Muhammad-anaskhon Khakimjon ogli (Galaxy International Interdisciplinary Research Journal, 2023)
Computer graphics is considered a separate department of information communication technology, and it is important to solve problems of an artistic and creative nature in open conditions from algorithmic thinking. It should be noted that the purpose of education is to use the computer as an educational tool, which is a modern level of education informatization, and the wide development of electronic educational resources in various subjects, testing and control of the computer. we consider it permissible to confess. This leads to the expansion of the content, forms and methods of education. At the same time, in order to create a consistent and didactically appropriate educational environment, it is necessary to emphasize the need to maintain a certain balance between new and optimal methods of traditional teaching and educational technologies.